2016
DOI: 10.1136/bmjdrc-2015-000123
|View full text |Cite|
|
Sign up to set email alerts
|

Design of and rationale for the Japan Diabetes Optimal Integrated Treatment study for 3 major risk factors of cardiovascular diseases (J-DOIT3): a multicenter, open-label, randomized, parallel-group trial

Abstract: ObjectiveMultifactorial intervention including the management of levels of blood glucose (BG), blood pressure (BP), and lipids has been suggested to decrease cardiovascular disease (CVD) risk. However, the target ideal and feasible levels for these individual parameters have not been fully evaluated. In this study, we examine the hypothesis that stricter control compared with the current targets in the Japanese guideline for BG, BP, and lipids could efficiently and safely reduce CVD risk.Research Design and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 20 publications
4
58
0
Order By: Relevance
“…The accurate assessment of individual risk can be of great value to guiding and facilitating the prevention of ASCVD 21. As early as in 1976, the Framingham Heart Study identified several risk factors and developed the first coronary heart disease risk equations 22.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate assessment of individual risk can be of great value to guiding and facilitating the prevention of ASCVD 21. As early as in 1976, the Framingham Heart Study identified several risk factors and developed the first coronary heart disease risk equations 22.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, three large-scale clinical trials supported by the Ministry of Health, Labor and Welfare are underway, i.e., Diabetes Outcome Intervention Trial (DOIT)-1, 2 and 3, the underlying rationales of which are the primary, secondary and tertiary preventions of T2DM [29,30]. This study, Japan Early Diabetes Intervention Study (JEDIS), complements these DOITs by comparing the effect on hyperglycemia of standard education and care for diabetes, i.e., lifestyle interventions, to that of additional administration of AHAs in patients with T2DM at its early stage without any complication.…”
Section: Background and Aimsmentioning
confidence: 99%
“…In Japan, J-Doit-3 study, in which 2,542 patients were randomly assigned either to ordinary therapy or intensive therapy with multiple targeting of HbA1c, blood pressure, LDL cholesterol, HDL cholesterol, triacylglycerol, and BMI purposed to suppress these values within the normal range. 6 A primary outcome occurred in 109 patients in the intensive therapy group and in 133 patients in the conventional therapy group (hazard ratio [HR] 0.81, p=0.094). Only cerebrovascular events were significantly less frequent in the intensive therapy group (HR 0.42, p=0.02), but hypoglycemia occurred in 41.1% patients in the intensive treatment vs. 22.3% in the control group.…”
Section: Progression Rate Of Ckd/dkd Is Recently Reported Bymentioning
confidence: 99%